The crystal structure of (4-hydroxybenzenesulfonate)-k1O-6,6′-((1E,1′E)- (ethane-1,2-diylbis(azaneylylidene))bis(methaneylylidene)) bis(2-methoxyphenol)-κ2N,N,μ2O,O,κ2O, O)-(methanol)-cobalt(II) sodium(I), C25H27CoN2NaO9S - Zhang Shaoliang; Wang Yanlan; Li Shanshan (Zeitschrift für Kristallographie - New Crystal Structures)
C25H27CoN2NaO9S, monoclinic, P21/c (no. 14), a = 12.8169(11) Å, b = 7.9965(7) Å, c = 25.597(2) Å, β = 91.530(2)°, V = 2622.5(4) Å3, Z = 4, Rgt(F) = 0.0611, wRref(F2) = 0.1596, T = 298 K.